The Comparative Study of Image Exaggeration in Old and New Iranian and Foreign Advertisement Based on Semiology - Hosseini, Seyyedeh Fatemeh; Majidi, Setareh (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This article has studied the image exaggeration in Iranian and foreign advertisement based on semiology. This study included articles and books that were written about semiotics, advertisements, and also exaggeration. “According to study results, while old and new Iranian and foreign advertisement has differed in latest decades, all of them have used exaggeration but in other way. In addition, there is relation between scientific use of exaggeration and modern societies.